Utilization of Chatbots for Novice Voters as An Alternative Tool to Help Verify Hoaxes - Samad, M. Yusuf; Setiono, Sigit; Sandikapura, M. Tesar; Sadiyatunnimah, Siti (Journal Social Politica, 2025)
Social media users, especially youth netizens or novice voters, have a strong attachment to social media but low political awareness. They do not feel comfortable showing their political expressions and connecting with political issues through their social media, thus indicating that they are vulnerable to fake news on social media. This situation can make them targets with dirty political intentions. This study aims to prevent youth netizens from being exposed to hoaxes, especially political hoaxes, through the use of Chatbots. This research was carried out through five stages, namely literature study, needs analysis, system design, system testing, and ending with documentation and report creation. The proposition in this study is that Chatbot can be used as an alternative effort to prevent youth netizens from being exposed to political hoaxes by using news verification technique features such as check the source, check the fact, check the images and check the date. The research suggestion is that Chatbot still has many limitations in its features so that further researchers can develop existing features specifically and comprehensive